Preparation and characterization of rice starch and transition metal stearates filled polypropylen - Malini, Subramaniam (2018)
The high versatility of synthetic plastics in terms of mechanical properties and durability has become a deteriorating factor of natural environment. In response to these issues, this study has been directed towards development and application of degradable plastics as an alternative to replace commodity non degradable plastics. Untreated rice starch (URS), treated rice starch (TRS) and transition metal stearates (TMS) were used as fillers and incorporated with polypropylene (PP). URS, TRS and TMS filled PP samples were prepared through extrusion and injection molding technique. URS and TRS were mixed with PP with a concentration of 10, 20, 30, 40 and 50 wt % respectively. Composition of TMS (CoSt3 and FeSt3) of 0.1, 0.3, 0.5, 0.7 and 0.9 phr was blended with PP. The prepared blends were characterized by tensile properties such as tensile strength (TS), tensile modulus (TM) and percentage of elongation at break (EB). The thermo-oxidative properties were studied by using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Degradability of blends was studied by using enzymatic degradation and accelerated weathering test. The degradation properties and surface morphologies were observed using fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) analysis. The results indicated that TS and TM of URS and TRS filled PP samples reduced as the composition of starch increases. The results indicated that maximum TS and TM of both CoSt3 and FeSt3 at concentration of TMS of 0.5 phr. DSC analysis showed that enthalpy and crystallinity of URS and TRS filled PP samples dropped as the composition of URS and TRS increased from 10- 50 wt % meanwhile crystallinity of PPFe5 samples were much higher than PPCo5 samples. Furthermore, higher Tmax in PP/TRS compared to PP/URS signified that the incorporation of TRS improved the thermal stability of the blends with the increase in the composition of starch (10-50 wt %). TGA results showed that PPCo5 has a higher Tmax as compared to PPFe5 and CoSt3 exhibits higher decomposition temperature as compared to FeSt3. During enzymatic degradation, URS and TRS filled PP samples experienced highest weight reduction after the 10, 20 and 30 days for 50 wt % URS and TRS. The weight loss in both PPCo5 and PPFe5 samples are almost negligible after enzymatic degradation. Significant discoloration was observed in both URS and TRS filled PP samples after accelerated weathering test. Same test showed that the ability of CoSt3 as pro-oxidant is more deteriorating than FeSt3 as observed in visual observation and SEM analysis of samples. The incorporation of URS, TRS and TMS into PP matrices exhibits some significant changes on the properties of plastic blends been produced. In all the formulation, it was observed decrease in mechanical and thermal properties but a significant improvement in the degradability of samples can be observed. Substitution of PP matrix with fillers can improve its susceptibility towards degradation. From the data analysis, TMS acts as best filler among all the three fillers been blended with PP followed by TRS and URS. Conclusively, filling of natural filler and pro-oxidants into synthetic plastics can be a great solution to solve the environmental issues caused by non-degradable plastic wastes.